60 is the new 40: preparing for better bone health in later life - Westbury, Leo; Gaba, Kamran; Bevilacqua, Gregorio; Fuggle, Nicholas; Dennison, Elaine (Frontiers in Aging, 2025)
ObjectiveIn this study we evaluated associations between nutritional factors, including calcium supplementation, and outcomes of fracture and cardiovascular mortality. We chose to report both outcomes as an illustration of the importance of nutritional factors in midlife to heart disease as this may be more impactful for supporting behavior change strategies, particularly in men.MethodsThis study was nested in the Hertfordshire Cohort Study, a community dwelling cohort of 2,997 adults (47% women) who were extensively phenotyped at baseline and followed up for 20 years using Hospital Episode Statistics linkage.ResultsMean (SD) age at baseline was 65.7 (2.9) among men and 66.6 (2.7) among women. There was some evidence that better diet quality was related to reduced risk of hip fracture after adjustment for sex (hazard ratio (95% CI): 0.82 (0.67, 1.00) per SD higher prudent diet score). Dietary calcium intake was not associated with either any fracture or hip fracture. Taking calcium supplements was associated with an increased risk of any fracture, possibly because of reverse causality as calcium supplements will typically be prescribed following an osteoporotic fracture. A higher dietary calcium intake was protective against cardiovascular-related mortality, while taking calcium supplements led to no excess risk (p = 0.870). Higher prudent diet scores, indicative of better diet quality, were related to other beneficial lifestyle choices such as reduced odds of ever smoking [odds ratio (95% CI) per SD higher diet score: 0.69 (0.63,0.74)], and higher physical activity (SD difference in physical activity score per SD higher diet score: 0.06 (0.02,0.10)).ConclusionWe have demonstrated the commonality of lifestyle factors to adverse clinical outcomes of fracture and heart disease in older adults. These data might be used in behavior change strategies aimed to improve nutrition and linked factors in midlife.